2024
DOI: 10.1002/saj2.20623
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a multiple‐row Tamarix windbreak on grain size parameters of aeolian sand flux

Abbas Miri,
Nicholas P. Webb

Abstract: Understanding the effects of windbreaks on aeolian sediment transport rates, and the size distribution of aeolian sediments transported through them, is important for designing windbreaks to optimize their wind erosion mitigation benefits. This field study determines the size distribution of aeolian sediments upwind (x = −100 m), within (x = 100 and 256 m) and downwind (x = 448 and 560 m) (where x is the distance from the first row of windbreak) of a multi‐row Tamarix windbreak as the basis for further investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 93 publications
(205 reference statements)
0
1
0
Order By: Relevance
“…When vegetation is restored on mobile sandy land, the changes in the airflow patterns caused by vegetation affect the distribution of sediments. Miri and Webb, (2024) found that, due to the blocking and trapping effects of vegetation, an inflection point was observed in the changes in the sorting, Sk, and Kg downwind of the vegetation [17]. The average particle size is higher on the upwind side of the windbreak and decreases with the increasing downwind distance within the windbreak.…”
Section: Introductionmentioning
confidence: 99%
“…When vegetation is restored on mobile sandy land, the changes in the airflow patterns caused by vegetation affect the distribution of sediments. Miri and Webb, (2024) found that, due to the blocking and trapping effects of vegetation, an inflection point was observed in the changes in the sorting, Sk, and Kg downwind of the vegetation [17]. The average particle size is higher on the upwind side of the windbreak and decreases with the increasing downwind distance within the windbreak.…”
Section: Introductionmentioning
confidence: 99%